Determination of Separation Efficiency of Hydrocyclone Used Pre-Filter in Micro Irrigation at Different Inlet Velocities and Sand Diameters - Cafer Gençoğlan; Hayri Şahin; Serpil Gençoğlan (Journal of Agricultural Sciences)
Hydrocyclones are used as pre-filter to reduce suspended particles in irrigation water on the subsequent filters. The aim of the study was to determine separation efficiency (SE) of hydrocyclones, called H1, H2 and H3 according to inlet/outlet diameters, at water velocities of 1.0 (V10), 1.5 (V15) and 2.0 (V20) ms-1, and sands diameter of 0.5 (D05), 1.0 (D10), 1.5 (D15), 2.0 (D20) and 2.5 (D25) mm. Therefore, a hydrocyclone laboratory test system was constituted using a water tank, motor pump, inverter, flowmeter, valve, hydrocyclone, disk filter, and polythene pipe. Separation efficiencies were calculated by dividing amounts of sand collected in collection box by feeding amount of sand. The lowest average separation efficiency was determined as 37% at H1V10D05 treatment and the highest ones as 97% at both H2V20D10 and H3V20D20, and the other ones changed between two values. Average separation efficiencies resulted as 69%, 88% and 88% for H1, H2 and H3 hydrocyclones, and 71%, 84% and 90% for V10, V15 and V20 water velocities, and 78%, 82%, 82%, 83% and 84% for D05, D10, D15, D20 and D25 sand diameters, respectively. Besides these, average separation efficiency for three parameters was 82%. Since the inlet size of H2 is smaller than that of H3 and its SE was higher than that of H1 and equal to that of H3, the most suitable hydrocyclone was determined as H2 to be used in the micro irrigation. The highest average separation efficiency was 90% at a water velocity of 2.0 ms-1. According to separation efficiency of the hydrocyclone, the optimum water velocity in the inlet of the hydrocyclone was determined as 2.0 ms-1. The separation efficiency of hydrocyclone showed that the efficiencies increased with increasing water velocity from 0.5 ms-1 to 2.0 ms-1 and sand diameters from 0.5 to 2.5 mm. In separation efficiency for micro irrigation, water velocities and suspended materials play crucial roles as well as hydrocyclone mechanical properties.